Longitudinal trends of HIV drug resistance in a large Canadian cohort, 1996–2016. (February 2018) - Rocheleau, G.; Brumme, C.J.; Shoveller, J.; Lima, V.D.; Harrigan, P.R.
Abstract: Objectives: We aim to identify long-term trends in HIV drug resistance before and after combined antiretroviral therapy (cART) initiation. Methods: IAS-USA (2015) mutations were identified in 23 271 HIV protease-reverse transcriptase sequences from 6543 treatment naïve adults in British Columbia. Participants who started cART between 1996 and 2014 were followed until April 2016. Equality of proportions test was used to compare the percentage of participants with acquired drug resistance (ADR) or transmitted drug resistance (TDR) in 1996, to those in 2014. Kaplan-Meier was used to estimate time to ADR in four drug resistance categories. Multivariable regression odds ratios (OR) of ADR for select clinical variables were determined by 5-year eras of cART initiation. Results: The proportion of individuals with ADR declined from 39% (51/132) to 3% (8/322) in 1996–2014 (p <0.0001), while the proportion with TDR increased from 12% (16/132) to 18% (59/322) (p 0.14). The estimated proportions of individuals with ADR rose to 29% (NNRTI), 28% (3TC/FTC), 14% (other nRTI), and 7% (PI) after >16 years of therapy. After 5 years on therapy, participants initiating cART in 1996–2000 had 5.5-times more 3TC/FTC ADR, 5.3-times more other nRTI ADR, 4.7-times more NNRTI ADR, and 24-times more PI ADR than those starting in 2011–2014. The individuals with highest odds of developing ADR in 1996–2010 were adherent to regimens at levels between 60% and 80%, which shifted to <40% adherent in 2011–2014. Conclusions: HIV drug resistance transitioned from being primarily selected de-novo to being driven by TDR. Among those who started treatment in the past 5 years, ADR is rare and observed mostly in the lowest adherence strata. Graphical abstract: